SUSTAINABLE DEVELOPMENT OF THE UKRAINIAN BEEKEEPING INDUSTRY - Tetiana Senchuk; Ihor Peliukhnia; Vitaliia Didenko (Baltic Journal of Economic Studies, 2022)
The results of an interdisciplinary systematic study of sustainable development of beekeeping in order to improve its institutional support are highlighted. The state documents (laws, concepts, strategies) concerning the development of agriculture and beekeeping are analyzed. It was found that the existing institutional support for the development of beekeeping is insufficient to fully realize the potential of the industry. The international criteria of sustainable development and their application to agriculture and beekeeping industry of Ukraine are generalized. The role of beekeeping in the implementation of the Sustainable Development Goals of Ukraine until 2030 is substantiated. The factors and conditions influencing the development of beekeeping and improvement of its production capacities are studied. It is proved that many problems can be overcome by improving the system of state regulation of the industry and creating sufficient institutional support. For the first time, criteria and a system of indicators for sustainable development of beekeeping have been developed, which are grouped into 7 blocks: state regulation / management; education, education and science; material, technical and financial support; primary production and processing of products; market and sales of products; food safety, veterinary support, epizootic welfare; environment and biodiversity. The formulated goals, criteria and indicators of sustainable regional development of beekeeping will improve the system of institutional support of the industry and develop a monitoring system to assess its progress and development.